2023
DOI: 10.3390/cancers15143686
|View full text |Cite
|
Sign up to set email alerts
|

Promising Highly Targeted Therapies for Cholangiocarcinoma: A Review and Future Perspectives

Abstract: To overcome the poor prognosis of cholangiocarcinoma (CCA), highly targeted therapies, such as antibody-drug conjugates (ADCs), photodynamic therapy (PDT) with/without systemic chemotherapy, and experimental photoimmunotherapy (PIT), have been developed. Three preclinical trials have investigated the use of ADCs targeting specific antigens, namely HER2, MUC1, and glypican-1 (GPC1), for CCA. Trastuzumab emtansine demonstrated higher antiproliferative activity in CCA cells expressing higher levels of HER2. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Antibody–drug conjugates (ADCs) are novel drug delivery mechanisms with two primary components: An antibody capable of targeting proteins expressed on the cell surface as well as a ‘payload’ of a cytotoxic chemotherapeutic agent [ 55 ]. Several promising cell surface protein targets have been identified that are under pre-clinical investigation for the treatment of cholangiocarcinoma.…”
Section: Molecular Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody–drug conjugates (ADCs) are novel drug delivery mechanisms with two primary components: An antibody capable of targeting proteins expressed on the cell surface as well as a ‘payload’ of a cytotoxic chemotherapeutic agent [ 55 ]. Several promising cell surface protein targets have been identified that are under pre-clinical investigation for the treatment of cholangiocarcinoma.…”
Section: Molecular Targetsmentioning
confidence: 99%
“…Yashima et al conducted a pre-clinical study evaluating an ADC comprised of an HER-2-targeting antibody in conjunction with a trastuzumab emtansine payload in the CCA cell line. The study demonstrated that cell death was increased in HER-2 overexpressing CCA cells when compared to HER-2 negative cells by IHC GPC-1 is a cell surface proteoglycan receptor that contributes to cellular growth and proliferation by acting as a co-receptor with other pro-growth cellular receptors [ 55 ]. GPC-1 overexpression has been demonstrated in up to 47% of CCA tumor specimens [ 56 ].…”
Section: Molecular Targetsmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is an effective modality for tumor treatment, [ 1 , 2 , 3 ] and its application in the management of malignancies, such as cholangiocarcinoma (CCA), [ 4 , 5 , 6 ] has demonstrated definitive therapeutic benefits. Besides its direct cytotoxicity toward tumor cells, PDT exhibits immunomodulatory properties supported by accumulating evidence.…”
Section: Introductionmentioning
confidence: 99%